O Jornal dos Trabalhadores Rurais Sem Terra e seus temas: 1981-2001 - Bezerra, Antonio Alves (2011)
The present work analyses the material produced and published by the Jornal dos Trabalhadores Rurais Sem Terra (Landless Rural Workers Newspaper) during the period from 1981 to 2001, and unveils the historical and political trajectory of the MST (Movimento Sem Terra Landless Workers' Movement), as well as of its leaders hereby personified by the figure of the rural landless worker, in that their experiences are narrated not as victims, but as historic figures devoted to the fight against the social exclusion process to which they were historically submitted to, with the land reform constituting their main claim. The survey carried out reveals that the JST (Landless Workers Newspaper) has during its trajectory registered intervention initiatives by the movement, as well as the participation of other entities and solidarity institutions offering support in order to collaborate with the multiple needs of the rural landless workers: the land reform and social justice in rural areas. In this regard, the survey took on the challenge of giving visibility to the articles published by the JST, not just because it would publish movement records, but to fulfill the desire to recover and historicize its actions, practices, discourses and its representations faced with landless workers aspirations. The following narrative is based on the interpretation and analysis of an extensive bibliography contemplating themes related to the land issue, political disputes involving the rural workers articulated by the Landless Workers Movement and by non-governmental organizations that took part in the project defended by this movement. Faced with this challenge, the research took a timeframe of approximately twenty years of JST publications and gave preference to the interpretation and analysis of editorials, interviews with movement leaders and articles of opinion written by politicians, catholic intellectuals and leftist academics, as well as the analysis of news and images published by the newspaper. For such, material that was selected and published by the CPT (Comissão Pastoral da Terra Pastoral Land Commission) was used in order to understand the relationship between newspaper s discourse and the information provided by the Cadernos Conflitos no Campo (Field Conflict Notebooks) published by this entity, particularly those regarding rural violence data. The research entitled O Jornal dos Trabalhadores Rurais Sem Terra e Seus Temas (The Landless Rural Workers Newspaper and its Themes 1981-2001) contributes towards understanding the stages of operation of the landless workers newspaper, uncovering its interfaces, objectives, language, its political opposition and its reading public. It also reveals the location and circulation numbers. This is information that provides the construction of a narrative in order to assure that it is understood not only as an object of communication for rural workers, but above all, as a subject of struggle and a briefer for the land reform project and social justice in rural areas and cities defended by the MST